Depth and Patterns of Adnexal Involvement in Primary Extramammary (Anogenital) Paget Disease: A Study of 178 Lesions From 146 Patients. (November 2016) - Konstantinova, Anastasia M.; Shelekhova, Ksenya V.; Stewart, Colin J.; Spagnolo, Dominic V.; Kutzner, Heinz; Kacerovska, Denisa; Plaza, Jose A.; Suster, Saul; Bouda, Jiri; Pavlovsky, Michal; Kyrpychova, Liubov; Michal, Michal; et al.
Abstract : Abstract: Extramammary Paget disease (EMPD) is a rare neoplasm usually presenting in the anogenital area, most commonly in the vulva. Adnexal involvement in primary EMPD is a very common feature and serves as a pathway for carcinoma to spread into deeper tissue. The depth of carcinomatous spread along the appendages and the patterns of adnexal involvement were studied in 178 lesions from 146 patients with primary EMPD. Hair follicles and eccrine ducts were the adnexa most commonly affected by carcinoma cells. The maximal depth of involvement was 3.6 mm in this series. When planning topical therapy or developing novel local treatment modalities for EMPD, this potential for significant deep spread along adnexa should be taken into account.